Effect of Developed Mobile Application on Undergraduates Academic Performance in Computer Science - Ebenezer Omolafe Babalola; Eyiyemi Veronica Omolafe (Universitas Pendidikan Indonesia (UPI), 2022)
This study is to investigate the effect of the Mobile Application developed on the academic performance of undergraduates in computer science at the University of Ilorin, Nigeria. Quasi-experimental design of pre-test, post-test non-randomized control group design was used to compare the performance of students who were exposed to Mobile Applications to learn Computer Science concepts and those who were taught through conventional methods. The computer science performance test (CSPT) was administered to the control and experimental groups as pretest and posttest. The sample size was chosen at random from 200 students. The instruments developed are mobile applications (DMP) and CSPT. CSPT was tested and a reliability coefficient of 0.86 was obtained using the Kuder Richardson KR-20. Two research questions and one hypothesis were formulated. The findings show that the experimental group is better than the control group with an average difference of 1.59. Male students did better than female students in the experimental group. There was no significant difference in the performance of male and female students in the two groups. This study concludes that the mobile application has a positive effect on student academic achievement. It is recommended, among other things, that University lecturers should take advantage of the potential of mobile technology applications in teaching.